Evaluation of enrichment, transport, and detection methods relating to Shiga toxin-producing Escherichia coli (STEC) - Baumann, Nicholas W. L. (Kansas State University, 2015)
Shiga toxin-producing Escherichia coli (STEC) are Gram negative rod-shaped bacteria that are causative agents of foodborne disease. While natural flora in the gastrointestinal tracts of bovines and other ruminants, certain enterohemorrhagic STEC strains cause serious or even fatal disease when ingested. In 2012, the USDA identified six STEC serotypes (O26, O45, O103, O111, O121, O145) as particularly dangerous (in addition to O157:H7; STEC-7) based upon data from the Centers for Disease Control and Prevention and designated them adulterants in raw ground beef, its component materials, and non-intact raw beef products. This research addressed three important components for detection of the recently declared STEC adulterant serotypes. Part one evaluated traditional E. coli O157 selective enrichment media, and additional media types and additive levels, for STEC-7 cultural amplification. Buffered peptone water (BPW), universal pre-enrichment broth (UPB), tryptic soy broth (TSB), TSB with 8 mg/L novobiocin, Escherichia coli broth (EC), and EC with 5, 8, and 20 mg/L novobiocin added were evaluated. EC broth performed equally well compared to non-selective media types, but addition of novobiocin supplement, typically used to suppress overgrowth by background flora, suppressed non-O157 STEC growth. Higher levels of novobiocin inhibited most serotypes. Part two tested the ability of transport media to maintain original STEC-7 concentrations as samples are transported to analytical laboratories. Transport media BPW, maximum recovery diluent (MRD), and Cary-Blair transport medium (CB) were inoculated with individual STEC serotypes and held at 4 or 10 °C for 72 h. Growth/survival curves indicated that CB maintained STEC-7 populations nearest to inoculation levels during storage at either temperature. Part three, part of a field study determining STEC-7 prevalence rates for cattle, hides and dressed carcasses, compared qualitative results generated by two molecular-based detection systems (BioControl Assurance GDS® and Neogen NeoSeek™), analyzing 576 selectively enriched beef carcass sponge samples collected from a commercial processing facility. The GDS and NeoSeek systems indicated 28.7 and 6.1 percent presumptive positive rates for STEC-7, respectively. It was speculated the higher GDS prevalence rate was due to false-positive determinations from the mixed culture enrichments, as viable STEC-7 cells were not recovered by immuno-magnetic bead culture isolation.
Keywords: STEC; Enrichment; Transport; PCR; Food Science (0359)